EXPERIMENTAL GROWTH OF QUARTZ IN PETROLEUM ENVIRONMENT. PART I: PROCEDURES AND FLUID TRAPPING - Teinturier S.; Pironon J. (My University, 2004)
The quartz-water-oil-gas system has been experimentally studied with the objective of investigating the trapping of petroleum and aqueous inclusions in quartz at different water/oil (W/O) ratios (0/100, 5/95, 10/90, 20/80, 50/50, 100/0). Experiments were carried out in both a gas-pressure autoclave (GPA) under CH4 pressure control, up to 250°C and 212 bar, and in a fluid-pressure autoclave (FPA) up to 350°C and 400 bar. High p-T conditions have notably allowed the growth of quartz at high oil saturation levels (W/O ratios from 10/90 to 50/50). Petroleum inclusions have been synthesised inside quartz microfractures (W/O ratios from 0/100 to 50/50; 209–350°C; 175–400 bar), and also inside quartz overgrowths (W/O ratios from 10/90 to 50/50; 289–350°C; 350–400 bar). Aqueous inclusions have been synthesised in presence of oil inside quartz microfractures from 185°C-163 bar up to 400°C-400 bar, and inside quartz overgrowth from 277°C-330 bar. Synthesised petroleum inclusions are representative of the parent oil up to 250°C. At 350°C, evidence of a cracking process has been observed with the consequent formation of methane. The segregation of the oil/gas/water column inside the GPA autoclave may also have prevented methane diffusion into the water phase when oil is present. This experimental approach shows that the trapping of fluid inclusions and the formation of quartz cement, under conditions of high oil saturation, have not been suppressed or prevented.